2022
DOI: 10.1093/sf/soac034
|View full text |Cite
|
Sign up to set email alerts
|

Embedded Distress: Social Integration, Gender, and Adolescent Depression

Abstract: In adolescence, teens manage close friendships while simultaneously evaluating their social position in the larger peer context. Conceptualizing distinct local and global network structures clarifies how social integration relates to mental wellbeing. Examining local cohesion and global embeddedness in the context of key factors related to mental health, such as gender and friends’ depression, can further distinguish when the structure and content of social integration relate to higher and lower depressive lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The findings also suggested that women were more likely than men to have experienced normalscale depression. Although depression can afflict people of any gender, there are significant patterns and distinctions in the occurrence, manifestation, and management of depression that are specific to gender (Copeland, 2023). Table 3 presented that for those respondents who were single, the results showed a high leaning toward depression.…”
Section: Resultsmentioning
confidence: 99%
“…The findings also suggested that women were more likely than men to have experienced normalscale depression. Although depression can afflict people of any gender, there are significant patterns and distinctions in the occurrence, manifestation, and management of depression that are specific to gender (Copeland, 2023). Table 3 presented that for those respondents who were single, the results showed a high leaning toward depression.…”
Section: Resultsmentioning
confidence: 99%